2010
DOI: 10.1002/med.20219
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase 1B Inhibitors: A Molecular Level Legitimate Approach for the Management of Diabetes Mellitus

Abstract: Diabetes mellitus is a systemic disease responsible for morbidity in the western world and is gradually becoming prevalent in developing countries too. The prevalence of diabetes is rapidly increasing in industrialized countries and type 2 diabetes accounts for 90% of the disease. Insulin resistance is a major pathophysiological factor in the development of type 2 diabetes, occurring mainly in muscle, adipose tissues, and liver leading to reduced glucose uptake and utilization and increased glucose production.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 189 publications
(195 reference statements)
3
67
0
1
Order By: Relevance
“…100,101 In mice, genetic ablation of protein tyrosine phosphatase 1B (PTP-1B) results in enhanced insulin sensitivity. 102 ISI-113175 (ISIS Pharmaceuticals), an antisense oligonucleotide PTP-1B inhibitor (100-200 mg injected weekly), has completed a phase 2 trial in patients with type 2 diabetes on stable, maximal doses of SU.…”
Section: 99mentioning
confidence: 99%
“…100,101 In mice, genetic ablation of protein tyrosine phosphatase 1B (PTP-1B) results in enhanced insulin sensitivity. 102 ISI-113175 (ISIS Pharmaceuticals), an antisense oligonucleotide PTP-1B inhibitor (100-200 mg injected weekly), has completed a phase 2 trial in patients with type 2 diabetes on stable, maximal doses of SU.…”
Section: 99mentioning
confidence: 99%
“…Способность ингибиро-вания цитоплазматической фосфатазы PTP1B явля-ется основанием и перспективным направлением поиска новых лекарственных средств для лечения СД2. Однако большинство исследований в данном направлении ведется на уровне молекулярного кон-струирования и синтеза высокоселективных, до-ступных для перорального приема ингибиторов, и анализа зависимости между химической структу-рой, физико-химическими свойствами и функцио-нальной активностью полученных соединений [56].…”
Section: активация и потенцирование инсулиновой сигна-лизации улучшеunclassified
“…Several experiments have also demonstrated that the knockout of PTP1B in mice can result in insulin hypersensitivity, even in a high-fat diet. [1][2][3][4][5][6] Therefore; small molecular inhibitors of PTP1B are promising drugs for curing type II diabetes. The full length of PTP1B consists of 435 amino acids, constituting the major cellular form; however, only a shorter length of 298 or 321 residues is typically considered in biochemical studies.…”
Section: Introductionmentioning
confidence: 99%